Producing in situ data from a distance with mobile instant messaging interviews(MIMIs): examples from the COVID-19 pandemic - Kaufmann, Katja; Peil, Corinna; Bork-Hüffer, Tabea (International journal of qualitative methods, 2021)
Researching people in their chaotic and complex everyday lives is challenging for researchers at any time but especially during the application of social distancing measures. In this article, we make the case for the methodical potential of mobile messengers such as WhatsApp for qualitative mobile in situ research. We exemplify the productive use of the Mobile Instant Messaging Interview (MIMI), a research method developed by Kaufmann and Peil in 2020, to study participants’ everyday life in real-time. Based on two case studies from geography and communication studies conducted during the COVID-19 pandemic, we expound our experiences in the practical application of the MIMI approach and give recommendations. We conclude that MIMIs are a low-cost, easily feasible and short-term implemented approach for research interests across disciplines and possessing great potential for exceptional circumstances like the COVID-19 pandemic. They allow direct access to the practices and experiences of people in situ and in real-time that would otherwise stay hidden and inaccessible to social sciences. The method is suitable for research projects of any size, and can be applied as part of multi- and mixed methods designs and as well for longitudinal designs. Nonetheless, the MIMIs have to be well prepared, demand smart ways of nudging participants into elaborating their responses and require careful coordination between larger teams of researchers.